Information Pour Le Développement Durable De La Santé – Cas De L’usage Des Réseaux Sociaux Dans La Lutte Contre Le Cancer De La Prostate En Côte d’Ivoire - Pascal, Gnamien Kouamé (European Scientific Journal, ESJ, 2018)
Prostate cancer is a pathology that causes casualties among the male population in Côte d'Ivoire. This pandemic kills silently but can be cured at the early stage of detection. All the actors in the fight against this pathology have mainly focused on the classical channels of communication and nonmedia. In the era of the information society, there is, however, a culture of digital technology in Côte d'Ivoire where the use of social networks is now part of the habits. While mass communication campaigns hinder efforts to raise awareness for early detection, more discreet and more customizable social networks have the advantage of reaching men who feel demeaned and humiliated when it comes to the «shameful, humiliating and dishonorable» disease of prostate cancer. The objectives of this research are to assess the impact of prostate cancer awareness campaigns on male population through traditional channels of communication and to analyze the determinants of the evolution of prostate cancer, despite all actions taken to propose solutions to curb the evolution of the disease. With the quantitative and qualitative approaches, the hypothesis that shows that there is a significant relationship between the evolution of prostate cancer among the male population and the late detection of this disease was confirmed. The communication strategies proposed by the various actors will then be effective, provided that social networks are associated with conventional media and non-media.